Ethicomedicolegal aspects of the COVID-19 health services in preparing regulations and intermediaries for clinical dispute resolution: a systematic review (Medical Journal of Indonesia, 2022)
BACKGROUND The COVID-19 pandemic has caused many medical, ethical, and medicolegal changes, including constant adjustments in service guidelines. Continuing to revise healthcare regulations and guidelines can potentially cause clinical disputes or medical negligence that require ethical and legal solutions. This study aimed to determine the ethical and medicolegal aspects of the potential factors that cause clinical disputes during the pandemic and provide anticipative solutions to national ethicomedicolegal policies. METHODS A systematic literature search in PubMed, ScienceDirect, ClinicalKey, and Google Scholar was performed using keywords “clinical dispute,” “ethics,” “medicolegal,” “ethicolegal,” and “COVID-19”. The inclusion criteria were articles that contained information on shortage, justice, ethical distribution in intensive care, the possibility of lawsuits and disputes among stakeholders during the pandemic, and stakeholders’ roles in managing the pandemic. Key evidence was analyzed and synthesized following national ethicomedicolegal policies. RESULTS We identified 19 articles from the 4 databases. Based on the literature, the main ethicomedicolegal impact of the COVID-19 pandemic appears in 3 aspects: (1) a shortage of fair and ethical intensive care services with fair and ethical distribution efforts, (2) legal protection for medical personnel from legal charges while providing health services during the pandemic, and (3) the government’s role in managing the pandemic together with the stakeholders involved. CONCLUSIONS Ethicomedicolegal clinical dispute management and its norms require an update, especially when deciding the complexity of COVID-19 service standards. Ethicomedicolegal professionals are needed as intermediaries to manage cases of clinical disputes and to implement fair malpractice criteria in Indonesia.